Polatuzumab vedotin plus bendamustine and rituximab or obinutuzumab in relapsed/refractory follicular lymphoma: a phase Ib/II study - Flowers, Christopher R; Matasar, Matthew J; Herrera, Alex F; Hertzberg, Mark; Assouline, Sarit; Demeter, Judit; McMillan, Andrew; Mehta, Amitkumar; Opat, Stephen; Trnňný, Marek; Musick, Lisa; Hirata, Jamie; et al. (Haematologica, 2024)
Follicular lymphoma (FL) is the most common type of indolent non-Hodgkin lymphoma. Despite treatment advances that have improved outcomes for patients with relapsed or refractory (R/R) FL, many patients still die from progressive disease or treatment-related toxicities. In the phase Ib/II GO29365 study (clinicaltrials.gov 02257567), the safety and efficacy of polatuzumab vedotin plus bendamustine and rituximab (Pola-BR) versus bendamustine and rituximab (BR) alone, and polatuzumab vedotin plus bendamustine and obinutuzumab (Pola-BG) as a single-arm cohort were evaluated in patients with R/R FL. Following the phase Ib safety run-in, patients were randomized 1:1 to receive Pola-BR or BR alone in the phase II stage; a separate non-randomized Pola-BG cohort was examined in the phase Ib/II expansion stage. Primary endpoints included safety and tolerability (phase Ib) and positron emission tomography complete response (PET-CR) rate by independent review committee (phase II). Overall, 112 patients were enrolled (phase Ib safety run-in: Pola-BR, N=6; phase II randomized cohort: Pola-BR, N=39; BR, N=41; phase Ib/II expansion cohort: Pola-BG, N=26). PET-CR rates were 66.7% (phase Ib safety run-in, Pola-BR); 69.2% (phase II randomized, Pola-BR); 63.4% (phase II randomized, BR); and 65.4% (phase Ib/II expansion Pola-BG). There was a higher occurrence of cytopenias with Pola-BR and Pola-BG than with BR; serious adverse events were more frequent with Pola-BR (61.4%) and Pola-BG (46.2%) than with BR (29.3%). Overall, this analysis does not demonstrate a benefit of adding Pola to BR or BG regimens for patients with R/R FL.
Keywords: Lymphoma, Large B-Cell, Diffuse; Humans; imunokonjugáty; Antineoplastic Combined Chemotherapy Protocols; Antibodies, Monoclonal, Humanized; protokoly protinádorové kombinované chemoterapie; Lymphoma, Follicular; monoklonální protilátky; Antibodies, Monoclonal; rituximab; Rituximab; Immunoconjugates; difúzní velkobuněčný B-lymfom; humanizované monoklonální protilátky; folikulární lymfom; Bendamustine Hydrochloride; lidé; bendamustin hydrochlorid